Exploring Students’ Perceptions on the Utilization of QuillBot in Writing Paragraph - Puput Handriani; Utami Dewi (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
This study aims to explore high school students' perceptions of the benefits and challenges of using the Grammar Checker and Translate features on QuillBot in writing English paragraphs. This study uses a qualitative descriptive approach. Data were collected thru closed questionnaires given to 23 twelfth-grade students, semi-structured interviews with 4 selected participants, and documentation analysis in the form of screenshots of QuillBot usage. The data were analyzed using thematic analysis. The research results show that 54.18% of students strongly agree that the Grammar Checker feature helps improve the accuracy of grammar and sentence structure, 54.18% strongly agree that the Translate feature makes the translation process easier, and 50.00% strongly agree that QuillBot boosts confidence in writing. However, 70% of students agree that they rely on the Grammar Checker and Translate features when writing. Additionally, 68% of students disagreed that QuillBot's translation results are often inaccurate, although some students reported contextual discrepancies in certain situations. This study concludes that QuillBot can support the paragraph writing process thru improved language accuracy, ease of translation, and student confidence, but its use needs to be balanced with the development of independent writing skills.